Quilling: The perks of creating art pieces using papers / Nur Syazwani Halim - Halim, Nur Syazwani (2022)
Quilling, also known as paper filigree, is the art of rolling, pinching, shaping, gluing and arranging paper strips to make beautiful designs and decorative patterns. The roll of paper strips can be done with fingers, a pin, a toothpick/skewer, or a slotted tool; a special needle-like instrument tailored for quilling. Colourful strips of papers with different widths and thickness can be quilled to make beautiful patterns for greeting cards, jewellery, boxes, ornaments, miniatures and many more.